Morphology of Helicobacter pylori as a result of peptidoglycan and cytoskeleton rearrangements - Paweł Krzyżek; Grażyna Gościniak (Gastroenterology Review)
Helicobacter pylori is a Gram-negative, microaerophilic bacterium colonising the gastric mucosa. Normally, this bacterium has a spiral shape, which is crucial for proper colonisation of the stomach and cork-screwing penetration of dense mucin covering this organ. However, H. pylori may also form curved/straight rods, filamentous forms and coccoid forms. This morphological variability affects nutrient transport and respiration processes, as well as motility, the ability to form aggregates/biofilms, and resistance to adverse environmental factors. For this reason, a more accurate understanding of the molecular determinants that control the morphology of H. pylori seems to be crucial in increasing the effectiveness of antibacterial therapies directed against this microorganism. This article focuses on the molecular factors responsible for peptidoglycan and cytoskeleton rearrangements affecting H. pylori morphology and survivability. In addition, the existence of proteins associated with modifications of H. pylori morphology as potential targets in therapies reducing the virulence of this bacterium has been suggested.